PENGARUH KONSENTRASI DAN FREKUENSI APLIKASI PUPUK URINE SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI KERITING (Capsicum annuum L.) - Andi Hasnaniah; St.Subaedah St.Subaedah; Netty Syam (Percetakan Umi Toaha Makassar, 2017)
Red chili plant a bush-shaped plant and is widely used as a flavor enhancer in food spicy. Demand for the chili continue to increase in line with population growth. This research was conducted at the location of Farmers Group Source Rezeki, Toddopulia Village, District Tanralili Maros which lasts from March to June 2016. This study aims to analyze the effect of the concentration and frequency of urine sapii applications on the growth and yield of curly red pepper. This study was conducted using a randomized block design with factorial 2 factors. The first factor is the treatment of cow urine concentration consisting of three levels ie 20 ml / liter of water, 40 ml / liter of water, and 60 ml / liter of water. The second factor is the frequency of application of cow urine which consists of two levels ie 2 weeks and 4 weeks. The results showed that the concentration of 40 ml / liter of water and frequency of fertilizer application of cow urine in 2 weeks give better effect on the growth and yield of chilli curls with the highest plant height of 85.83 cm, the number of branches stalk 44.42, the fastest flowering age 46 02 days, the number of fruit per plant fruit 143.62, weighs 625.42 grams of fruits per plant and fruit production per hectare of 11.47 tonnes.